ANALISIS PENGARUH CUSTOMER SENSITIVITY DAN SOURCING FLEXIBILITY TERHADAP SUPPLY CHAIN AGILITY DAN KINERJA PERUSAHAAN (Studi Kasus pada Industri Kuliner Kreatif di Kota Semarang) - Hardian, Davin; Kusumawardhani, Amie (Diponegoro Journal of Management, 2019)
The purpose of this study is to analyze customer sensitivity to supply chain agility, analyze sourcing flexibility to supply chain agility, supply chain agility to company performance, customer sensitivity to company performance, and sourcing flexibility to company performance.The population used in this study were all creative culinary industry SMEs, where the respondents were people in the city of Semarang. The number of samples used was 117 respondents. The method of collecting data through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques using AMOS 22.0 analysis tools.The results of this study indicate that customer sensitivity has a positive and significant effect on supply chain agility, sourcing flexibility has a positive and significant effect on supply chain agility, supply chain agility has no positive effect on company performance, customer sensitivity has a positive and significant effect on company performance, and sourcing flexibility positive and significant effect on company performance. The theoretical implications of this research reinforce the theories that have been developed from previous research. The managerial implications of this study suggest that the creative culinary industry in Semarang City find out and respond to real customer desires, and build good relationships with raw material suppliers.